The Effects of Seismic Anisotropy on Regional Seismic Wave Propagation - Park, Jeffrey (1997)
Crustal rocks can be highly anisotropic, due to (1) oriented minerals, (2) oriented cracks, and/or (3) thin layers of material with different elastic stiffnesses. Crustal Love and Rayleigh surface waves couple strongly for anisotropic structures that do not possess a vertical axis of symmetry, and cause explosions to generate significant shear motion on the transverse component of seismograms. We developed theory and 1-D layered-media synthetic seismogram codes for anisotropy with an arbitrary axis of symmetry. One code version can synthesize surface waves with periods 100 > T > 0.4 sec. Another code version can synthesize teleseismic body wave reverberations up to 5 Hz. We determined that a tilted axis of symmetry enhances Love-Rayleigh coupling and the scattering of P-waves (compressional) to S-waves (shear). Using P-S scattering, we found evidence for strong (> 10%) anisotropy in the deepest and shallowest crustal layers beneath seismic station ARU (Arti, Russia), an 'open' seismic observatory proximal to the Novaya Zemlya nuclear test site. We also developed a wavelet-based signal processing algorithm that picks out correlated 'signals' from uncorrelated 'noise' in an optimally bandpassed manner. Using the Terrascope regional array in California we applied this algorithm to reconstruct, for a single correlated signal anomalous amplitudes and polarizations at individual stations, allowing more 'signal' to be recovered than via standard 'stacking.'